2015
DOI: 10.1080/07448481.2015.1075994
|View full text |Cite
|
Sign up to set email alerts
|

Self-focused and other-focused resiliency: Plausible mechanisms linking early family adversity to health problems in college women

Abstract: Objectives: This study examined whether self-focused and other-focused resiliency help explain how early family adversity relates to perceived stress, subjective health, and health behaviors in college women. Participants: Female students (n = 795) participated between October 2009 and May 2010. Methods: Participants completed self-report measures of early family adversity, selffocused (self-esteem, personal growth initiative) and other-focused (perceived social support, gratitude) resiliency, stress, subjecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 65 publications
(113 reference statements)
0
18
0
Order By: Relevance
“…Students' ability to cope successfully when faced with the academic, social, and financial stressors of college life has a major impact on both their future health and academic success (Coleman, Zawadzki, Heron, Lenny, & Smyth, 2016). Adaptive resilience interventions during the challenging time of transition to college may lower stress, improve emotional awareness, increase resilience, and foster a sense of belonging, thus facilitating the attributes needed for improved health, academic engagement, and athletic success.…”
Section: Resultsmentioning
confidence: 99%
“…Students' ability to cope successfully when faced with the academic, social, and financial stressors of college life has a major impact on both their future health and academic success (Coleman, Zawadzki, Heron, Lenny, & Smyth, 2016). Adaptive resilience interventions during the challenging time of transition to college may lower stress, improve emotional awareness, increase resilience, and foster a sense of belonging, thus facilitating the attributes needed for improved health, academic engagement, and athletic success.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical Association Among the six studies, three found a significant association [50,61,78]. All the significant associations were negative.…”
Section: Number Of Cigarettes Smoked (N = 6)mentioning
confidence: 94%
“…Among the 16 studies that found no association [39, 40, 46-50, 52-55, 57, 58, 60-62], 4 studies investigated the association with dimensional measures of self-esteem (i.e., contingent self-esteem, implicit self-esteem and decisional selfesteem) [39,40,48,62] and 2 were based on female participants [50,53]. One study found an association with implicit self-esteem but not with explicit self-esteem [59].…”
Section: Alcohol Consumption (N = 26)mentioning
confidence: 99%
See 2 more Smart Citations